Mechanisms regulating muscular hypertrophy - Menghini, C.; Riva, L.; Rocca, M. (EWF Scientific Magazine, 2019)
With a brief analysis of only some of the aspects that can affect muscle growth, it seems clear that everything that includes specific training goes well beyond the simplifications sometimes abused in this field. If you want to maximize the hypertrophic stimulus, it requires a different method of approach to the problem rather than the simple prescription of an exercise or a training volume. Therefore, a working method that can integrate and manage training variables over time is necessary in order to obtain a complete training stimulus that includes the right doses of mechanical tension, metabolic stress and muscle damage. It is necessary to plan and periodize the training aimed at hypertrophy, with the clearest vision on how every aspect of training can affect the main variables of hypertrophic development.